A Strategic Analysis of Impact of the WTO Accession on China's Telecommunication Industry - ZHANG, LEI (2007)
By the end of 2007, China Telecommunication substantially keeps going open up. However there are still opportunities along with challenges after accession to WTO. It is important to analyze the current situation of China's telecommunication industry.